Chemosystematic aspects of polyisoprenylated benzophenones from the genus Clusia - Anholeti,Maria Carolina (2015)
Benzophenone derivatives are special metabolites that arouse great scientific interest. The Clusiaceae family is known for producing large amounts of benzophenone derivatives with several isoprene residues on their structures, which are responsible for the observed complexity and structural variety in this class of substances, and also contribute to their biological activities. Clusia is an important genus belonging to Clusiaceae, with 55 different polyisoprenylated benzophenones identified so far. These substances were analyzed from biosynthetic and chemosystematic points of view, allowing the determination of characteristics regarding their production, accumulation and distribution within this genus. Polyisoprenylated benzophenones found in Clusiashowed a high prenylation degree, with 2 to 5 isoprene units and a greater occurrence in flowers and fruits. Section Cordylandra showed a very similar occurrence of 2,4,6-trihydroxybenzophenone derivatives and bicyclo[3.3.1]nonane-2,4,9-trione derivatives, the majority of them with 4 isoprene units. In section Anandrogyne there is a predominance of simple 2,4,6-trihydroxy-benzophenone derivatives, with 2 isoprene units, and in Chlamydoclusia predominates bicyclo[3.3.1]nonane-2,4,9-trione derivatives with 4 isoprene units. Although highly prenylated, these substances showed low oxidation indexes, which from an evolutionary perspective corroborates the fact that Clusiaceae is a family in transition, with some common aspects with both basal and derived botanical families.